THE STUDY AND DESIGN OF DRAMA ACTIVITIES IN EDUCATION TO ENHANCE SURVIVAL SKILLS IN EARLY PRIMARY SCHOOL CHILDREN - Chokchaipatthamaporn, Thanaporn; Pattayanon, Porawan (Fine Arts Journal: Srinakharinwirot University, 2025)
Background and Objectives: Currently, the mortality and injury rates among early primary school children due to various accidents remain a critical issue that requires urgent attention. Children in this age group still need to develop essential skills to cope with potentially hazardous situations such as drowning, road accidents, and falls from heights. Therefore, it is necessary to enhance learning processes that promote survival skills in children. This study aims to design Drama-in-Education (DIE) activities that effectively develop survival skills in early primary school children. Methods: This study employed a qualitative research approach based on Drama-in-Education theory, Thorndike's Theory of Learning, and Piaget’s Cognitive Development Theory. The research involved designing DIE activities that align with children's cognitive and behavioral development. The design process consisted of five key steps: (1) analyzing baseline data, (2) defining the objectives of the activities, (3) designing content and learning processes, (4) piloting the activities and gathering expert feedback, and (5) refining the activities to ensure they are appropriate for the learners’ context. Key Findings: The data analysis revealed that the designed DIE activities achieved a high level of content validity, with an Index of Item-Objective Congruence (IOC) of 1.00 for activities 1-8 and 10-12, accounting for 91.67%. Activity 9 had an IOC value of 0.67 and was subsequently revised to better align with children’s real-life experiences. The revised activities placed greater emphasis on the role of the facilitator in stimulating children's thinking, incorporated more hands-on demonstrations, and created more realistic scenarios to enhance engagement and learning outcomes. Implications of the Study: The design of DIE activities to enhance children's survival skills presents a viable approach for integration into school curricula and extracurricular programs. Utilizing drama as an educational tool enables children to learn through direct experience, develop situational awareness, and apply acquired knowledge in real-life situations. Moreover, grounding the activity design in learning and cognitive development theories ensures that the activities are developmentally appropriate and maximize their effectiveness in fostering survival skills in children. Conclusions and Future Study: The findings suggest that Drama-in-Education can be an effective strategy for developing children's survival skills. However, this study primarily focused on designing and evaluating the content validity of the activities. Future research should involve implementing these activities with actual student groups to assess their tangible impact. Additionally, expanding the scope of the activities to address a wider range of risk scenarios could further enhance children's ability to respond effectively to emergencies.